Biogenesis and function of extracellular miRNAs - Chihao Zhao; Xinlei Sun; Limin Li (ExRNA)
Abstract Mature microRNAs (miRNAs) are 18–24-nucleotide non-coding RNAs with post-transcriptional regulatory functions and have been documented as an essential cornerstone of the genetic system. Although the traditional idea suggests that RNA molecules cannot be stable in extracellular environments due to ubiquitous ribonuclease, miRNA has now been verified as circulating in various body fluids in a stable, cell-free form. By associating with microvesicles (MVs) or RNA-binding proteins, extracellular miRNAs can be actively secreted and transferred into recipient cells, where they regulate target genes. Importantly, extracellular miRNAs have been demonstrated as participating in various physiological and pathological processes in bodies and have significant roles in fetal-maternal crosstalk and cross-kingdom regulation. Furthermore, the abnormal expression of extracellular miRNAs has been shown to be associated with many diseases, making extracellular miRNAs promising novel noninvasive diagnostic markers. In this review, we summarize the recent literature on the biogenesis, delivery and uptake of extracellular miRNAs, elaborate on the regulating function of extracellular miRNAs between different cells and between individuals and highlight their therapeutic potential in clinical applications.